Reproductive performance of freshwater prawn Macrobrachium rosenbergii (De Man 1879) broodstocks grown on different diets (Journal of the Bangladesh Agricultural University, 2017)
An experiment was carried out during April to September 2013 to compare the reproductive performance of freshwater prawn golda (Macrobrachium rosenbergii) broodstocks fed on diets including 3 commercial (Mega -F1, SABINCO- F2 and CP- F3) and a laboratory formulated test feed (F4). Post larvae (PL) were collected from the river Kocha of district Pirozpur in April 2012 and nursed in the hapa (net cage) then reared in earthen ponds at the Fisheries Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh. The broods were fed with selective feeds since their PL stage. The feeding was continued till their maturity of both male and female up to berried females. The proximate composition of the feeds, F1 where crude protein, 33.49%, lipid 5.38%, carbohydrate 30.31%, F2-crude protein, 26.70%, lipid 5.50%, carbohydrate 34.34%, F3- crude protein, 38.90%, lipid 8.09%, carbohydrate 25.37% and treatment F4- crude protein 33.00%, lipid 11.13%, carbohydrate 25.43%. Feeds were supplied at 5% body weight twice at dawn (5:30-6:00 am) and dusk (5:30-7:30 pm) till the end of the experiment. The variation in most water quality parameters, temperature, alkalinity, DO, transparency, TDS, conductivity NO2 --N, PO4 - 3 and chlorophyll-a were insignificant; while parameters, water depth, pH, NH3-N and NO3 --N was found to vary significantly (p